ECB Communication: What Is It Telling Us? - Kaminskas, Rokas; Stukas, Modestas; Jurkšas, Linas (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
This study examines the changing nature of ECB communication and how it impacts euro area financial markets over the past two decades. We applied a combination of topic modelling and sentiment analysis for over 2000 public ECB Executive Board member speeches, as well as over 200 ECB press conferences. Topic analysis revealed that the ECB’s main focus has shifted from strategy and objectives, at the inception of the euro area, to various policy actions during the global financial crisis and, later on, to policy instruments. Sentiment analysis showed a trend of a more negative communication tone during periods of turmoil and a gradual shift to a more dovish monetary policy tone over time. Regression analysis revealed that sentiment indices had the expected impact on financial market indicators, while press conferences exhibited substantially stronger effects than speeches. Among the different topics covered in policymaker speeches, only the topic on ECB instruments led to repricing in euro area markets.